Increased Maternal Care Rescues Altered Reinstatement Responding Following Moderate Prenatal Alcohol Exposure. (14th August 2019) - Olguin, Sarah L.; Zimmerman, Amber; Zhang, Haikun; Allan, Andrea; Caldwell, Kevin C.; Brigman, Jonathan L.
Abstract : Background: Fetal alcohol spectrum disorders (FASD) commonly include deficits in learning, memory, and executive control that can have a severe negative impact on quality of life across the life span. It is still unclear how prenatal alcohol exposure (PAE) affects executive control processes, such as control over reward seeking, that lead to inappropriate behavior later in life. Learning and reinstatement of a previously learned response after extinction is a simple, well‐validated measure of both acquisition of a rewarded instrumental response and sensitivity to reward and reward‐associated cues. We investigated the effects of PAE on learning, extinction, and reinstatement of a simple instrumental response for food reward. Next, we assessed the effectiveness of an early intervention, communal nest (CN) housing, on increased reinstatement of an extinguished response seen after PAE. Methods: To assess the effects of PAE on control over reward seeking, we tested male and female PAE and saccharine (SAC) controls raised in a standard nest (SN) on the acquisition, extinction, and food reward–induced reinstatement of an instrumental response utilizing a touch screen‐based paradigm. Next, in order to examine the effects of an early‐life intervention on these behaviors, we tested PAE and SAC mice raised in a CN early‐life environment on these behaviors. Results: PAE mice readily acquired and extinguished a simple touch response to a white square stimulus. However, PAE mice showed significantly increased and persistent reinstatement compared to controls. Increased maternal care via rearing in CN slowed acquisition and sped extinction learning and rescued the significantly increased reinstatement responding in PAE mice. Conclusions: Together these results demonstrate that even moderate PAE is sufficient to alter control over reward seeking as measured by reinstatement. Importantly, an early‐life intervention previously shown to improve cognitive outcomes in PAE mice was sufficient to ameliorate this effect. Abstract : In this study we investigated the effects of prenatal alcohol exposure (PAE) on learning, extinction, and reinstatement of an instrumental response for a food reward. Next, we tested whether an early intervention, communal nest (CN) housing would blunt the increased reinstatement response seen after PAE. We show that CN reduced the increased reinstatement in standard nest (SN) PAE mice, suggesting increased maternal care during the early post‐natal period may be an effective approach for improving control over reward seeking.